2016
DOI: 10.11591/ijeecs.v1.i2.pp329-340
|View full text |Cite
|
Sign up to set email alerts
|

On Sparse Compression Complexity of Speech Signals

Abstract: <p>In this paper, we have addressed the issue of the sparse compression complexity for the speech signals. First of all, this work illustrated the effect of the signal length on the complexity levels of Matching Pursuit (MP) and Orthogonal Matching Pursuit (OMP) algorithms. Also, this paper introduced a study of possibility to reduce that complexity by exploiting the shared atoms among the contiguous speech compressions. By comparing the shared atoms levels and a threshold level induced by an analytic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…). Summing up, the overall complexity of the OMP could be concluded to be O)(kMN ) as stated in an earlier work [31]. As for the nOMP methodology, its complexity could be shortly written as O(k 2 M √ e th +1 α ).…”
Section: B Complexity Analysismentioning
confidence: 83%
“…). Summing up, the overall complexity of the OMP could be concluded to be O)(kMN ) as stated in an earlier work [31]. As for the nOMP methodology, its complexity could be shortly written as O(k 2 M √ e th +1 α ).…”
Section: B Complexity Analysismentioning
confidence: 83%
“…This review is also significant, since CS has been implemented in various research areas and applications, such as compressive imaging [24]- [26], biomedical applications [27], [28], pattern recognition [29], [30], sound processing [31]- [34], video processing [35], [36], and microelectronics applications [37], [38], and its most well-known implementation is in the field of communication systems, such as wireless networks and antenna [39]- [47]. It has been shown that this field is growing and has a wide opportunity for exploration using this technique of compression.…”
Section: Algorithm 1 Omp Algorithmmentioning
confidence: 99%